Molecular, Biochemical, and Phenotypic Identification of Phenol and Cresol Degrading Acinetobacter baumanni Strain Selected from Al-Rumaila Oil Well - Noor Mohammad Ali1 , Aamal Ghazi Mahdi Al-Saadi1 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: phenol and cresol are dangerous compounds that have harmful effects on aquatic life, plantsand, many other organisms. Therefore, it is necessary to effectively eliminate these compounds to protectthe environment.Aim: The aim of this study is to select and characterizebacterial strain(s) from oil contaminated soils andtesting its ability for biodegrading phenol and cresol.Methods: Biochemical tests were performed in addition to morphological and molecular detection through16S rRNA analysis to identify the selected strain after growing on Mineral salts medium (MM) containingphenol or cresol . The residual concentration of phenol and cresol was analyzed over the time period bymeans of the 4-aminoantipyrine assay .Results: the selected strain was identified as Acinetobacter baumannii strain HILLA-1, and it was able toremove 100% of the phenol at all the used concentrationsafter 48 h. This strain was also able to degrade 100%of cresol at concentrations (25,50,75,100,200 ppm /L) and99.37%,88.69%,and 94.73% at concentrations(300,400,500 ppm /L) respectivelyafter 48 h.Conclusion: The selected and identified Acinetobacter baumannii strain HILLA-1 can provide a putativesource for bioremediation of phenol and cresol contaminated environments.